TEMPORARY AND CASUAL EMPLOYMENT AS FORMS OF FLEXIBLE EMPLOYMENT - Gavranić, Ratko (Glasnik Advokatske komore Vojvodine, 2025)
Temporary and casual employment is in the legal system of the Republic of Serbia one of the most significant form of flexible employment. Although it’s very significant, there are not many papers in our literature, which are dedicated exclusively to this type of flexible employment. However, given the fact that work flexibilization and flexible employment are extremely popular topics, there are many papers in which the issue of temporary and casual employment is mentioned within this topic. This paper is dedicated to the issue of how much this form of labor contributes to the flexibility of work, and where are the limits of work flexibilization, that is in which point the abuse of temporary and casual work begins, precisely flexploitation of the people who perform this work, as well as their legal position. The central part of the paper on the abuse of temporary and casual work will be perceived through the viewpoints of judicial practice, considering that, as it is previously mentioned above, there are not many papers in literature that are exclusively dedicated to this topic, and therefore not many viewpoints on the issue of abuse of the same, and judicial practice is, regarding this issue, numerous.